Individual and environmental determinants of burnout among nurses. Issue 3 (July 2019) - Rees, Clare S.; Eley, Robert; Osseiran-Moisson, Rebecca; Francis, Karen; Cusack, Lynette; Heritage, Brody; Hegney, Desley
Objective: Burnout is a significant problem affecting the nursing workforce and is associated with significant personal suffering and high rates of nurse turnover. Efforts to further understand the variables that explain burnout are needed. The aim of this cross-sectional study was to examine both environmental and individual factors that may explain burnout among nurses. Method: We recruited 1848 Australian nurses to complete several online questionnaires measuring the practice environment (Practice Environment Scale of the Nursing Work Index), burnout (Professional Quality of Life Scale), trait negative affect ( Spielberger State-Trait Anxiety Inventory form Y2 ) and resilience (Connor Davidson Resilience Scale). Correlational analysis as well as hierarchical regression was used to determine the relative importance of variables in explaining burnout scores. Results: All of the practice environment scales were significantly related to burnout in the negative direction, and these relationships were above .3 for all except the relationship scale ( r = –.256) and the participation in hospital affairs scale ( r = –.285). Overall, the regression model accounted for 62% of the variance in nurse burnout scores. Trait negative affect, resilience and two aspects of practice environment (Manager sub-scale and Staffing sub-scale) all explained significant variance in burnout scores. The largest contribution came from the two individual variables (resilience and trait negative affect) that together explained 55% of the variance in burnout scores. Conclusions: Findings suggest that health service administrators should provide nursing staff with education and support to build individual resilience. Workplaces that attend to staffing and resource issues and have managers who provide high levels of support to their staff appear to be essential strategies to help prevent nurse burnout.